2017
DOI: 10.1111/jcms.12609
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to Different National Interests: Voting Behaviour on Genetically Modified Organisms in the Council of the European Union

Abstract: Does voting behaviour in the Council of Ministers reflect different national interests? In this article, we explore this question by studying requests for authorization of genetically modified organisms (GMOs). The fact that GMOs constitute a highly contentious issue in the European Union enables us to look underneath the 'culture of consensus' which usually characterizes voting behaviour in the Council. We argue that the focus on one issue area can help us to discover more specific voting patterns than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Bailer et al . () find that the presence of strong economic domestic interests dictate when a government decides to vote “no” or “abstain” in the Council (see also Mühlböck and Tosun ()). Public opinion – in particular the public's attitude towards EU integration – has also been shown to have an effect in a number of core policy areas (Hagemann et al, ).…”
Section: Signals and Voting In The Eu Councilmentioning
confidence: 99%
See 1 more Smart Citation
“…Bailer et al . () find that the presence of strong economic domestic interests dictate when a government decides to vote “no” or “abstain” in the Council (see also Mühlböck and Tosun ()). Public opinion – in particular the public's attitude towards EU integration – has also been shown to have an effect in a number of core policy areas (Hagemann et al, ).…”
Section: Signals and Voting In The Eu Councilmentioning
confidence: 99%
“…Thus, a number of recent findings based on quantitative voting analyses has contributed to our understanding of what drives governments' behaviour in the Council. Bailer et al (2015) find that the presence of strong economic domestic interests dictate when a government decides to vote "no" or "abstain" in the Council (see also Mühlböck and Tosun (2017)). Public opinionin particular the public's attitude towards EU integration has also been shown to have an effect in a number of core policy areas (Hagemann et al, 2017).…”
Section: Signals and Voting In The Eu Councilmentioning
confidence: 99%
“…A study from 2015 by EuropaBio (EuropaBio ) indicated that Denmark and Sweden tended to vote according to the scientific advice for GM applications in 2014, though perhaps not in every instant, and Finland is among the group of about 10 EU countries who always followed science in their votings in 2014. Mühlböck and Tosun () analysed the voting behaviour for GM events in the EC over the period 2004–2014 and found that Sweden and Finland are among the most permissive countries with nearly 100% of the votes in favour of GM approval, whereas Denmark is found somewhere in the middle of the EU‐28 list with about 60% of votes in favour and about 40% of votes against GM event authorizations. Also, a study by Smart et al () of the EU Member States' voting behaviour on GM events in 2003–2015 confirms this general picture.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…In the case of such a result, neither the rejection nor the acceptance of a regulatory proposal is permitted. The Commission has frequently experienced such 'no opinion' votes on proposals related to the (re)authorization of GMOs [22]. The parallel voting outcomes can be explained by the similarity of both comitology procedures [23] and the differences in opinion on the part of member states regarding both issues.…”
Section: Comparing the Politics Of Gmos And Glyphosatementioning
confidence: 99%